THE POSSIBILITY FOR PUBLIC GREEN OPEN SPACE PROVISION IN INFORMAL SETTLEMENT CASE STUDY OF KAMPUNG KEJAWAN LOR, SURABAYA - Shirleyana Shirleyana; Astri Anindya Sari (Journal of Architecture&ENVIRONMENT, 2013)
Green open space has been a worldwide issue. Big cities in the world have a higher concerns regarding open space provision. Researchers have proven that open space will improve the quality of life of people. However, problems of green space provision are also arising related to scarcity of land which is a common problem to cities with high density of population. One solution offered in big cities is converting vacant lot into pocket park. However, this solution could be different for informal settlement. The problems are worsened in this higher density area. The limited space and no proper infrastructure induce big problems such as health and social problems. This paper would like to find out the possibility to create such pocket park in the very limited space of informal settlement. The case study area looked at the informal settlements in coastal area in Surabaya, which is supposed to build the city image as waterfront city. The situation in the settlement has decreased over years and need a revitalization effort. This study used literature review to find solution of problems derived from the field observation. Pocket park could be an alternative solution which includes three successful factors: community participation, local identity, and support from community organization and government.